Gang: Culture : Eidos and Process - Crewe, Don (Oñati Socio-Legal Series, 2016)
The terms ‘gang’ and ‘culture’ are used with varying degrees of (im)precision in different fields of academe, media, public, and policy; and this paper will contend that this circumstance provides a fertile ground for the reification of these two concepts. It will suggest that this phenomenon of reification has already taken hold in various parts of the study of gangs more recently, and in cultural criminology in a more established way. This paper will deconstruct the concepts ‘gang’ and ‘culture’ and attempt to reconstruct them in a way that opens up the discourse of ‘gangs’ and ‘culture’ such that better sense may be made of the phenomena that these terms are intended to evoke.